Protein Glycoengineering: An Approach for Improving Protein Properties - Ma, Bo; Guan, Xiaoyang; Li, Yaohao; Shang, Shiying; Li, Jing; Tan, Zhongping (Frontiers in Chemistry, 2020)
Natural proteins are an important source of therapeutic agents and industrial enzymes. While many of them have the potential to be used as highly effective medical treatments for a wide range of diseases or as catalysts for conversion of a range of molecules into important product types required by modern society, problems associated with poor biophysical and biological properties have limited their applications. Engineering proteins with reduced side-effects and/or improved biophysical and biological properties is therefore of great importance. As a common protein modification, glycosylation has the capacity to greatly influence these properties. Over the past three decades, research from many disciplines has established the importance of glycoengineering in overcoming the limitations of proteins. In this review, we will briefly summarize the methods that have been used to glycoengineer proteins, with a focus on strengths and weaknesses of different methods.